2022
DOI: 10.1038/s41560-021-00951-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxic potency-adjusted control of air pollution for solid fuel combustion

Abstract: The combustion of solid fuels, including coal and biomass, is a main anthropogenic source of atmospheric particulate matter (PM). The hidden costs have been underestimated due to lack of consideration of the toxicity of PM. Here we report the unequal toxicity of inhalable PM emitted from energy use in the residential sector and coal-fired power plants (CFPPs). The incomplete burning of solid fuels in household stoves generates much higher concentrations of carbonaceous matter, resulting in more than one order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…Figure c and d shows PM emissions and their related toxic potency (including cell-based ROS and cytotoxicity)-adjusted emissions originating from ships and diesel vehicles in 2020 in China. The estimation of PM-related toxic potency-adjusted emissions were detailed in our previous study . Although the population of diesel vehicles was substantially higher than that of ships, PM emissions in China from ship exhaust (61 thousand tons) were comparable to those from on-road diesel vehicles (64,000 tons) in 2020 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure c and d shows PM emissions and their related toxic potency (including cell-based ROS and cytotoxicity)-adjusted emissions originating from ships and diesel vehicles in 2020 in China. The estimation of PM-related toxic potency-adjusted emissions were detailed in our previous study . Although the population of diesel vehicles was substantially higher than that of ships, PM emissions in China from ship exhaust (61 thousand tons) were comparable to those from on-road diesel vehicles (64,000 tons) in 2020 .…”
Section: Resultsmentioning
confidence: 99%
“…The estimation of PM-related toxic potency-adjusted emissions were detailed in our previous study. 37 Although the population of diesel vehicles was substantially higher than that of ships, PM emissions in China from ship exhaust (61 thousand tons) were comparable to those from on-road diesel vehicles (64,000 tons) in 2020. 33 Furthermore, ship-emitted PMs dominate the overall PM-related toxic potency-adjusted emissions in the two subsectors, with relative contributions of 87.5% and 95.9% for ROS-and cytotoxicity-adjusted emissions, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Through the deployment of ACSM for an extended period (6 months) and in combination with the rolling PMF analysis, residential heating from solid fuel burning (wood, peat, and coal) was found to be one of the major OA sources in cold seasons of winter and spring, while long-range transport was found to play a more important role when heating activities were reduced in warmer seasons of summer. Domestic solid fuel burning can be a great health concern as studies have shown that solid fuel burning OA can be more toxic than other sources [ 9 , 15 ], although the toxicities of peat burning, the dominant solid fuel burning OA factor found in this region, remain poorly investigated in comparison with other solid fuels of wood and coal combustion. Considering that solid fuel burning emissions are directly linked to local heating activities, in theory, it can be reduced through the replacement of dirty fuels by cleaner fuels (e.g., gas or electricity) or using a more efficient wood stove instead of an open stove with no emission control [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organic aerosol (OA) is one of the most important components of PM, constituting 20–90% of the submicron PM (PM 1 ) mass [ 14 ]. Atmospheric OA contains thousands of organic molecules, which have been reported to be more toxic than inorganic aerosol, e.g., sulfate and nitrate [ 9 , 15 ]. OA can be directly emitted from emission sources of e.g., traffic [ 16 ] and biomass burning [ 17 ] and was, thus, termed as primary OA (POA), while secondary OA (SOA) is produced in the atmosphere from the oxidation of the precursor gases of volatile organic compounds [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous toxicological studies have also demonstrated varying toxic potencies in PM 2.5 of equal mass between cities and between sources and determined the quantitative contribution of certain components (e.g., metals, polycyclic aromatic hydrocarbons) to partially account for these discrepancies in toxicity. 19,20 This issue contains a critical review (Colonna et al)…”
Section: ■ Consensus and Puzzlesmentioning
confidence: 99%